Pengembangan Pemasaran Umkm Batik Tulis Untuk Meningkatkan Perekonomian Masyarakat Di Desa Genilangit Kecamatan Poncol Kabupaten Magetan - Nofitasari; Amri, Muhtadin (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
During the current pandemic, many people are unemployed, lack education, and lack knowledge about skills, so the purpose of this activity is training for the development of written batik marketing in Genilangit village. The actions we carry out can be helpful and also able to increase and foster enthusiasm for entrepreneurship for PKK mothers, especially young people, so that they are more enthusiastic about innovating and creating so that local people can live prosperously from their work. In addition to guiding the importance of innovation and entrepreneurship, we also conduct training on the digital world and ways to promote UMKM products to be well-known in the broader community. Within the Genilangit Village community, the marketing strategy still needs to be higher, so hand-written batik needs to be famous outside Genillangit Village. This service aims to help promote the market of Genilangit-written batik so that it is known in the wider community. Because in this day and age, social media is increasingly sophisticated, so it's easier to promote goods. As a good seller, you must sell in the right way so that consumers are satisfied with the products you sell, don't because selling online we ch by selling goods that don't match consumer orders because customers are the most important in buying and selling transactions.